(untitled) (International Journal of Engineering and Computer Science, 2014)
In the field of networks wireless sensor network consists of small, large number of sensing nodes which is having the sensing, computational and transmission power. But due to insecure nature of wireless communication, these networks are vulnerable to internal and external attacks. Moreover, routing protocols are designed, taking the consideration of power consumption not security as a goal. As security plays an important role in the ability to deploy and retrieve trustworthy data from a WSN. This paper introduces all kind of routing protocols with their advantages and disadvantages. We also present a survey of all kind of attacks and secure routing protocols which will help us to know about the present status of security in WSN. We also introduce the concept of multipath routing in WSN to provide the secure and reliable communication. At the end we have proposed the solution regarding security point of view for WSN.